First case report of spontaneous biliary pleural fistula diagnosed using near infrared region I/II fluorescence of indocyanine green - Peng, Yisheng; Fan, Jun; Zhu, Gang; Fang, Cheng; Peng, Fangyi; Zhang, Zeyu; Tian, Jie; Su, Song; Yang, Xiaoli; Li, Bo (Frontiers in Oncology, 2022)
We report a rare case of spontaneous biliary pleural fistula in a patient whose diagnosis was aided by the use of near-infrared I/II fluorescence imaging. When both 99mTc-mebrofenin hepatobiliary scintigraphy and CT examination were diagnostically difficult, we found strong fluorescent signals in the patient's pleural drainage fluid and sputum using NIR I/II fluorescence imaging, and therefore diagnosed the patient with a biliary pleural fistula. This provides a safe and effective test for diagnosing biliary pleural fistulas.